Changes of soil bacterial community composition and functional groups in different altitude gradients of Potentilla fruticosa shrub in eastern Qinghai-Tibet Plateau - Xie, Lele; Ma, Yushou; Wang, Yanglong; Ma, Yuan; Liu, Ying (Frontiers in Plant Science, 2025)
IntroductionSoil properties and extracellular enzyme activities are the key factors affecting microbial communities at different altitudes. It is very important to understand their distribution patterns along the elevation gradient for predicting the function of alpine ecosystems in response to climate change, especially in alpine shrub ecosystems, which are rarely studied.MethodsIn eastern Qinghai-Tibet Plateau Set up four sample plots with different altitudes (3400,3700,4000,4300 and 4300 m), Illumina I6S gene sequencing was used to analyze the changing law of soil bacterial community, and its diversity and influencing factors were discussed by combining correlation and redundancy analysis.ResultsThe results showed that the contents of soil total carbon, total nitrogen, water content, microbial biomass carbon, nitrogen, phosphorus and alkaline phosphatase were the highest, but the bacterial diversity was the lowest (Shannon and Pielou index); Dominant bacteria are different at different altitude gradients. Acidobacteriota is the most abundant at 3700, 4000 and 4300 m above sea level, while Verrucomicrobiota is the most abundant at 3700m above sea level; In addition, PCoA analysis showed that the community structure of soil bacteria changed significantly, with similar structures at 3700 , 4000 and 4300 m above sea level; Redundancy analysis (RDA) showed that soil properties (TC and BD) and enzyme activities (AG, BG and CBH) were the main factors affecting the bacterial community, while soil properties (TN), microbial biomass (MBC and MBN) and enzyme activities (AG and BG) all had significant effects on the functional groups of soil bacteria.ConclusionTo sum up, these results show that soil physical and chemical properties, microbial biomass, enzyme activities and bacterial communities have different responses to different altitude gradients.These studies provide a new perspective for us to deeply understand the driving factors of soil bacterial community variation along the elevation gradient. It is helpful to strengthen our awareness of the protection of Potentilla fruticosa shrub, and also provide basic information for the study of alpine ecosystem in this area.